2021
DOI: 10.1021/acs.langmuir.0c03569
|View full text |Cite
|
Sign up to set email alerts
|

Application of Localized Surface Plasmon Resonance Spectroscopy to Investigate a Nano–Bio Interface

Abstract: The accurate determination of events at the interface between a biological system and nanomaterials is necessary for efficacy and safety evaluation of novel nano-enabled medical products. Investigating the interaction of proteins with nanoparticles (NPs) and the formation of protein corona on nanosurfaces is particularly challenging from the methodological point of view due to the multiparametric complexity of such interactions. This study demonstrated the application of localized surface plasmon resonance (LS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…101 The analysis of Stern−Volmer plots for the interaction of glycosylated human transferrin and nonglycosylated recombinant human transferrin with Au NPs also confirmed that these proteins form stable complexes with NPs and the fluorescence is quenched following the static mechanism. 102 Barbero et al investigated the interaction of mucins of two types with Au NPs of three sizes and different capping ligands (cysteamine or thioglycolic acid). 103 They found that the affinity of proteins to NPs is affected to a greater extent by the capping agent rather than the size.…”
Section: K Pmentioning
confidence: 99%
“…101 The analysis of Stern−Volmer plots for the interaction of glycosylated human transferrin and nonglycosylated recombinant human transferrin with Au NPs also confirmed that these proteins form stable complexes with NPs and the fluorescence is quenched following the static mechanism. 102 Barbero et al investigated the interaction of mucins of two types with Au NPs of three sizes and different capping ligands (cysteamine or thioglycolic acid). 103 They found that the affinity of proteins to NPs is affected to a greater extent by the capping agent rather than the size.…”
Section: K Pmentioning
confidence: 99%
“…Proteins, for example, are known to bind directly on bare gold surfaces. However, this can have an impact on their stability and functionality 30 and can result in weakened target binding. Different immobilization methods have been developed in the past to address this challenge, as described above.…”
Section: Discussionmentioning
confidence: 99%
“…All microfluidic assays used a custom build LSPR instrument (figure S3 ) at IPHT-Leibniz. It consists of a halogen light source HL-2000-FHSA (Ocean Optics, USA), an optical fiber connected UV/VIS linear photodiode array spectrometer USB 2000+ (Ocean Optics, USA), a peristaltic pump (Ismatec Reglo-ICC, Cole-Parmer GmbH, Wertheim, Germany), a 2-way valve (Bio-Chem Fluidics Inc, Boonton, USA) for the waste and a custom designed 3D printed microfluidic chamber (figure S4 ) and sealing with two inputs and one output capillary at each channel side similar to an earlier published setup 28 30 . For some measurements single-use flow cells “Basic sensor platform II” (# 10001354, microfluidic chip shop GmbH, Jena, Germany) were used with adhesive tape gasket for Fl.…”
Section: Methodsmentioning
confidence: 99%
“…Proteins, for example, are known to bind quite well directly on bare gold surfaces. However, this can have an impact on their stability and functionality 27 and can result in weakened target binding. Different immobilization methods have been developed in the past to address this problem, as discussed before.…”
Section: Discussionmentioning
confidence: 99%
“…For all the micro uidic assays a custom build LSPR instrument was used. It consists of a halogen light source HL − 2000 − FHSA (Ocean Optics, USA), an optical ber connected UV/VIS linear photodiode array spectrometer USB 2000+ (Ocean Optics, USA), a peristaltic pump (Is-matec Reglo-ICC, Cole-Parmer GmbH, Wertheim, Germany), a 2-way valve (Bio-Chem Fluidics Inc, Boonton, USA) for the waste and a custom designed 3D printed micro uidic chamber and sealing with two inputs and one output capillary at each channel side similar to an earlier published setup [25][26][27] . For some measurements single-use ow cells "Basic sensor platform II" (# 10001354, micro uidic chip shop GmbH, Jena, Germany) were used with adhesive tape gasket for Fl.…”
Section: Lspr Instrumentmentioning
confidence: 99%